"See one, do one – or sometimes just do one". An ethnological analysis of the work practices of healthcare professional within the Greenlandic healthcare system. Issue 1 (1st January 2018) - Loop, Laura
ABSTRACT: Many healthcare professionals working in Greenland are employed on temporary contracts. This is a pressing issue within the Greenlandic healthcare system. The present thesis aims to explore the impact that the many temporarily employed persons have on the everyday work practices in the healthcare system. Special attention is devoted to the informants' own perception of their work practices as learning by doing . This thesis unboxes how the health personnel understands and practises learning by doing . It is shown how learning by doing contains aspects of disclaiming responsibility for work assignments. However, it also spurs on professional and personal development and drive. Furthermore, the thesis uncovers how the many temporarily employed healthcare workers create a dichotomy between the permanently employed healthcare professionals and those in short-term positions. Mutual engagement in patient care by the health personnel however facilitates cooperation and team spirit and thereby helps to break down the barriers between the two groups of employees. Methodologically, the examination draws upon qualitative empirical data, which the author has generated through extensive fieldwork within the Greenlandic healthcare system the fall of 2017.